Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2353/ajpath.2009.081115
|View full text |Cite
|
Sign up to set email alerts
|

Arginase Activity Mediates Retinal Inflammation in Endotoxin-Induced Uveitis

Abstract: Arginase has been reported to reduce nitric oxide bioavailability in cardiovascular disease. However, its specific role in retinopathy has not been studied. In this study, we assessed the role of arginase in a mouse model of endotoxin-induced uveitis induced by lipopolysaccharide (LPS) treatment. Measurement of arginase expression and activity in the retina revealed a significant increase in arginase activity that was associated with increases in both mRNA and protein levels of arginase (Arg)1 but not Arg2. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 57 publications
4
59
1
Order By: Relevance
“…n ϭ 6 for all groups; *P Ͻ 0.05 vs. control. expression is involved in vascular endothelial dysfunction in a number of disease states, such as hypertension, diabetes, atherosclerosis, ischemia-reperfusion injury, and inflammation (13,14,33,47,48). Despite an array of pathologic conditions associated with elevated arginase function, organs such as the liver require arginase for physiologic function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…n ϭ 6 for all groups; *P Ͻ 0.05 vs. control. expression is involved in vascular endothelial dysfunction in a number of disease states, such as hypertension, diabetes, atherosclerosis, ischemia-reperfusion injury, and inflammation (13,14,33,47,48). Despite an array of pathologic conditions associated with elevated arginase function, organs such as the liver require arginase for physiologic function.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of arginase has been reported to decrease blood pressure and improve vascular function of resistance vessels in adult hypertensive rats (2, 13). These findings thus suggest a central role for arginase in diseases in which vascular dysfunction is linked to elevated levels of angiotensin II (ANG II).We and others have found that inflammatory cytokines, reactive oxygen species (ROS), thrombin, LPS, and activation of the RhoA/ROCK pathway can elevate arginase expression and activity (16,26,33,48). RhoA/ROCK has also been indicated as an upstream regulator of mitogen-activated protein kinase (MAPK) family members such as p38 MAPK (22).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This is a model for uveitis which is a damaging ocular condition that can lead to severe vision loss and blindness [27]. The model is induced by injecting endotoxin (lipopolysaccharide, LPS) into mice, resulting in an ocular inflammation similar to human acute anterior uveitis such as the breakdown of blood-ocular barrier, increases in retinal inflammatory cytokine production, leukocyte attachment to retinal vessels, and leukocyte infiltration into anterior segments [2830]. After LPS injection, analysis of 3-nitratyrosine levels demonstrated that endotoxin induced significant nitration of retinal proteins (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Arginase can function as an immunosuppressive factor in the tumor environment (131), in viral (132), or in parasitic infection (133). However, this enzyme has also been identified as an important proinflammatory factor in numerous disease models (134)(135)(136). As inflammation decides the fate of HPV infection and arginase is an important regulator of inflammation and immunity, we investigated the interaction between DNCB-induced inflammation and HPV16.E7 protein in induction of arginase in K14.E7 transgenic mice.…”
Section:  the Aims Of This Study Are Tomentioning
confidence: 99%